2017
DOI: 10.1177/0081246317722931
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a group of South African psychologists’ well-being: competencies and contests

Abstract: The aim of this study was to establish the levels of well-being of South African psychologists by implementing a mixed method research design. Positive psychology was used as framework as psychosocial well-being is a core concept in this exciting subdiscipline in psychology. In the quantitative part of the study, participants (n = 279) completed questionnaires consisting of four standardised measures of well-being (The Mental Health Continuum Short Form, The Wagnild Resilience Scale, Meaningfulness in Life Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Studies on intrapersonal variables related to psychotherapists' wellbeing have confirmed the role of personality as well as self-care behaviors, including self-compassion and mindfulness practices, in maintaining a high quality of life in that profession (Rzeszutek et al, 2015 ; Yip et al, 2017 ; Hitge and van Schalkwyk, 2018 ; Rupert and Dorociak, 2019 ; Yela et al, 2020 ). It appears that greater care for the personal emotional balance of psychotherapists is a crucial, but highly understudied issue, both in the empirical field, as well as in relation to psychotherapists' training procedures involving various therapeutic modalities (Laverdière et al, 2018 ).…”
Section: Summary Of Findings and Main Conclusionmentioning
confidence: 97%
“…Studies on intrapersonal variables related to psychotherapists' wellbeing have confirmed the role of personality as well as self-care behaviors, including self-compassion and mindfulness practices, in maintaining a high quality of life in that profession (Rzeszutek et al, 2015 ; Yip et al, 2017 ; Hitge and van Schalkwyk, 2018 ; Rupert and Dorociak, 2019 ; Yela et al, 2020 ). It appears that greater care for the personal emotional balance of psychotherapists is a crucial, but highly understudied issue, both in the empirical field, as well as in relation to psychotherapists' training procedures involving various therapeutic modalities (Laverdière et al, 2018 ).…”
Section: Summary Of Findings and Main Conclusionmentioning
confidence: 97%
“…Only four studies within the literature have specifically eluded to the attributing factors to the mental health of industrial psychologists (c.f. Barnard & Fourie, 2007;Hitge These studies suggested that four factors could be significant contributors to and indicators of the mental health of industrial psychologists: (a) work-role fit, (b) meaningfulness, (c) work engagement and (d) whether an individual occupies a managerial or specialist function. Consequently, industrial psychologists with different mental health profiles may also differ with respect to their experiences of these factors, as well as the extent towards which these relate.…”
Section: Mental Healthmentioning
confidence: 99%
“…From this perspective, individuals subjectively judge the value of work-related tasks and goals in relation to their own ideals, values and norms (May et al, 2004). If tasks are deemed to be aligned to one's personal mission and vision, coupled with feelings that one is contributing to something larger than oneself and that one is making a ''difference'', then individuals will experience high levels of psychological meaningfulness (Hitge & Van Schalkwyk, 2018;Olivier & Rothmann, 2007).…”
Section: Meaningfulness and Mental Healthmentioning
confidence: 99%